Response of Maize (Zea mays L.) to Different Rates of Palm Bunch Ash Application in the Semi-deciduous Forest Agro-ecological Zone of Ghana - S. Adjei-Nsiah (Applied and Environmental Soil Science)
The effects of palm bunch ash (PBA) and mineral fertilizer application on grain yield and nutrient uptake in maize and soil chemical properties were studied in both the major and minor rainy seasons in the semi-deciduous forest agro-ecological zone of Ghana. In both the major and minor rainy seasons, the response of maize to four levels (0, 2, 4, and 6 tons per hectare) of palm bunch ash and 200 kg per hectare of NPK (15-15-15) application was evaluated using randomised complete block design. Results of the study showed that application of palm bunch ash significantly (P<0.05) increased soil pH, soil phosphorus, and exchangeable cations. Maize grain yield varied significantly (P<0.05) among the different treatments in both the major and minor rainy seasons. The highest maize grain yield of 4530 and 6120 kg ha-1 was obtained at PBA application rate of 2 tons ha-1 for the major and minor rainy seasons, respectively.